PENGEMBANGAN PERANGKAT PENILAIAN BERBASIS KELAS PADA MATA PELAJARAN BIOLOGI SMA KELAS XI - Mariani Natalina '; Evi Suryawati '; Siti Rukmana ' (Biogenesis, 2015)
The purpose of this research is to develop the classroom-based assessment on biology subjects for XI grade Senior high school. Assessment consists of seven graderoom-based assessment techniques. There are paper and pencil test, attitude, performance, product, project, self-assessment and portofolio. The development Class-based software is based on ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The development was conducted at Biology Education University of Riau and the limiting test was conducted at SMAN 8 Pekanbaru. The research held on January until April 2014. Used research and Development (R & D) design with ADDIE model. Subjects consisted of four Basic Competencies (KD) in the XI grade Senior high school. Data were collected by filling the validity of the assessment sheet by each validator which consists of internal and external validators. Collected datas were analyzed by descriptive statistics. Average results of the validity of class-based assessment are: 3.6 for the paper and pencil test, 3.7 for attitude assessment, 3.7 for performance assessment, 3.6 for product assessment, 3.6 for project assessment, 3.8 for self-assessment and 3.7 for portofolio assessment. On the last stage of the research, a limiting test on the XI grade senior high school. The results from validation, we can conclude that the class-based assessment in high school biology subjects class XI obtain the category of very valid and can be implemented in the learning process.Keywords : Biology Subject, Classroom-Based Assessment, Development